2016
DOI: 10.1007/s00330-016-4318-2
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of derived parameters from histograms following non-Gaussian diffusion modelling of diffusion-weighted imaging in a paediatric oncological cohort

Abstract: ObjectivesTo examine repeatability of parameters derived from non-Gaussian diffusion models in data acquired in children with solid tumours.MethodsPaediatric patients (<16 years, n = 17) were scanned twice, 24 h apart, using DWI (6 b-values, 0–1000 mm−2 s) at 1.5 T in a prospective study. Tumour ROIs were drawn (3 slices) and all data fitted using IVIM, stretched exponential, and kurtosis models; percentage coefficients of variation (CV) calculated for each parameter at all ROI histogram centiles, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
32
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 29 publications
6
32
1
Order By: Relevance
“…Referring to T 2 WI and DWI images, the region of interest (ROI) was manually outlined on the ADC map of the largest cross‐section of the tumor, and visually identified calcifications, large vessels, necrosis areas, and artifacts were excluded, then the software‐generated mean ADC value was recorded. For the repeated scanned data, the matching slice was set …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to T 2 WI and DWI images, the region of interest (ROI) was manually outlined on the ADC map of the largest cross‐section of the tumor, and visually identified calcifications, large vessels, necrosis areas, and artifacts were excluded, then the software‐generated mean ADC value was recorded. For the repeated scanned data, the matching slice was set …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, to use these parameters in the clinical assessment of lung cancer, the reproducibility of these quantitative parameters should be determined to know the magnitude of change in D, D*, f, and ADC that can be detected confidently. There is only modest literature on the reproducibility of IVIM in other organs . With regard to the lungs, Weller et al discussed the short‐term scanning reproducibility of ADCs of malignant lung lesions.…”
mentioning
confidence: 99%
“…Histogram analysis can provide information about whole tumors including minimum, maximum, mean, skewness and kurtosis values of the parameter distributions . More valuable information can be obtained from a histogram analysis of DKI parameters …”
mentioning
confidence: 99%
“…A number of previous studies have shown that the assessment of tumour heterogeneity is highly valuable for cancer diagnosis, prognosis, and treatment monitoring [1012]. Histogram analysis is a widely used tool for heterogeneity quantification, particularly for MRI features, which are not always well visualised with the naked eye [11, 13]. Two quantities calculated by using this method are uniformity (U) and entropy (E).…”
Section: Introductionmentioning
confidence: 99%